PELAKSANAAN PELAYANAN PRIMA PADA ACCOUNT REPRESENTATIVE ( AR ) DI KPP PRATAMA WONOCOLO SURABAYA - Nurmiati, Nurmiati; Yulianti, Tri; Kusbandrijo, Bambang (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
Implementation of Prima Services on Representative Account (AR) in KPP Pratama Wonocolo Surabaya. Account Representative is the officer in charge at the Pratama Tax Office, which has already applied modern administrative system. This research aims to gain an overview of the characteristics of excellent service implementation at the KPP Pratama Surabaya Wonocolo. The implementation of excellent especially by officials Account Representative (AR) departmend of supervision and and consultation. The data were obtained from observations and interviews with relevant parties, especially AR department of supervision and consultation at the KPP Pratama Surabaya Wonocolo and the taxpayer. The results of the interviews and the data collected were analyzed using descriptive method with interpretive approach. Results from the research showed that in general the officials Accounting Representative (AR) of KPP Pratama Surabaya Wonocolo indicates excellent service with good implementation, the overview of the implementation of service excellence at the KPP pratama Surabaya Wonocolo was shown with attitudes approach related to care, efforts to serve with the best act that is based on ability, attitude, attention, appearance, actions, and responsibilities. To support these actions must be supported by integrity, professionalism (accountability and commitment), synergy, services (sincerity and transparency) and ethical code. Meanwhile, to achieve the objective of satisfaction was shown with some of the responses from taxpayer in general. Â  Keywords : implementation, Accounting Representative, excellent service